Mempercepat Change Over di Mesin IMM - Jonathan Albertus Gunawan; I Nyoman Sutapa (Jurnal Titra, 2021)
PT. X is a daily use plastic packaging manufacturing company. The variety of the products produced causes PT. X to have many change over operation. The change over time for the IMM machine in production floor is taking too long causing delay in customer product fulfillment. Because of that it needs improvement. The chosen method to address this problem is Single Minute Exchange of Dies (SMED). The project was done by conducting an on-site observation and directly determined the machine and mold that is problematic. Pareto diagram, fishbone, and 5-whys analysis method were used to identify the root cause of the problem and the main factors contributes to it. The chosen machine and mold will be measured in time and analyzed directly using SMED. SMED analysis result will be used to create an improvement. Improvement that can be applied will be implemented immediately toward the affected machines and molds. The solution that has been implemented toward the machine and mold’s work methods has managed to reduce the amount of change over time by up to 45 percent.